Potentially inappropriate prescribing and its demographic and clinical correlates in older adults with atrial fibrillation: a population-based study. (3rd October 2022) - Amrouch, C; De Buyser, S; Dai, L; Larranaga, A C; Vetrano, D L; De Smedt, D; Petrovic, M
Abstract: Introduction: Older adults with atrial fibrillation (AF) have an increased risk of comorbidities and often take a combination of medicines. Moreover, it is known that anticoagulants tend to be underprescribed or underdosed in older patients with AF. Thus, it is important to evaluate the overall quality of prescribing because potentially inappropriate prescribing is associated with serious adverse events. Purpose: To assess the quality of prescribing and to analyze the association between potentially inappropriate prescribing with demographic and clinical variables in a Swedish urban older population with AF. Methodology: The Swedish National Study on Aging and Care is an observational longitudinal population-based study (baseline: 2001–2004) of adults aged 60 years or older (n=3363). We used the Screening Tool of Older Persons Prescriptions/Screening Tool to Alert doctors to Right Treatment (STOPP/START) version 2 algorithms (1) to assess the quality of prescribing. STOPP and START criteria identify potentially inappropriately prescribed medications and medications that are omitted but should have been prescribed, respectively. We could apply 72% of the STOPP criteria and 50% of the START criteria to the dataset. A hurdle negative binomial regression model was fitted to investigate the association between STOPP/START and age, sex, polypharmacy, and functional status indicated by activities of daily living. Results: We analyzed data on 293 participants with AF. STOPP and START criteria occurred in 53.6% and 63.5% of older patients with AF, respectively. The most frequently inappropriately prescribed drugs (STOPP) were anticoagulants (4.8%), hypnotic Z-drugs (19.1%), benzodiazepines (19.1%) and drugs contributing to anticholinergic burden (6.8%). The most frequently omitted drugs (START) were antiplatelets (26%), anticoagulants (26%), statins (14.3%), beta-blockers (17.7%), vitamin D (15.7%), calcium supplements (15.7%) and laxatives (16%). Polypharmacy (≥5 drugs; OR 3.45; 95% CI 1.85–6.44) was significantly associated with higher odds of having at least one STOPP criterion (Table 1). Disability (OR 2.56; 95% CI 1.26–5.21) was significantly associated with higher odds of having at least one START criterion. Among persons with at least one STOPP or START criterion, the estimated mean number of STOPP and START criterion were 2.35 (95% CI 1.36–4.09) and 2.49 (95% CI 1.48–4.21) times higher, respectively, in persons with high polypharmacy (>10 drugs) compared to those without polypharmacy. Conclusion: Potentially inappropriate prescribing and prescribing omissions were prevalent in this population of older adults with AF, beyond the well-known case of anticoagulants. Thorough multi-disciplinary medication reviews might improve quality of prescribing, especially in those with polypharmacy and functional impairment. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This project has received funding from the European Union's Horizon 2020 research and innovation programme under grant agreement No. 899871.